A bibliographic review of the Chelodesmidae of the Antilles and Bahamas (Diplopoda: Polydesmida) - Suriel, Carlos; Bueno-Villegas, Julián; Means, Jackson C.; Bouzan, Rodrigo Salvador (Zootaxa, 2024)
Among millipede groups found in the Antilles, the family Chelodesmidae is the most species diverse and well represented in collections. However, to date, there has not been a bibliographic review of the family for the region. Here we compile and review the literature for the Chelodesmidae of the Antilles and the Bahamas, clarify the family’s status for the region, and discuss the central deficits of its taxonomy and the most relevant obstacles for work in the group. The following information is documented for the region: 119 species in 24 genera and 5 tribes. Of the 24 genera, only 8 have been placed in tribes, and 20 are endemic to their respective islands, except for Amphelictogon (Cuba–Hispaniola), Chondrotropis (Hispaniola–Jamaica), Pandirodesmus (Guyana [mainland]–Trinidad and Tobago) and Lepturodesmus (Tobago–Venezuela). Here, Chelodesmidae represents a high species richness when compared to what is known for continental territories, for example in the state of São Paulo, Brazil (64 species) and Venezuela (38 species). Despite its impressive diversity, the Chelodesmidae of the Antilles have yet to be addressed using molecular phylogenetics, and the evolutionary and taxonomic relationships between genera within and outside of the Caribbean are poorly understood.